2016
DOI: 10.1111/jfpe.12353
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Extraction of Astaxanthin from Shrimp Waste (Penaeus Vannamei Boone): Effect on Yield and Antioxidant Activity

Abstract: High pressure extraction (HPE) of astaxanthin from shrimp (Penaeus Vannamei Boone) waste at different pressure (0.1-600 MPa) and holding times (0-20 min), and with different solvents (acetone, dichloromethane and ethanol) and solvent to solid ratios (10-50 mL/g) was evaluated, and extraction yields and quality of the extracts were determined. Antioxidant activity of the extract from HPE and conventional solvent extraction (at ambient pressure) were compared based on DPPH (1,1-diphenyl-2-picrylhydrazyl) and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…The DPPH radical scavenging activities of the MVH were determined as described by Li et al (2017) with slight modifications. Briefly, 1.0 mL of DPPH (0.1 mmol/L) diluted in ethanol was added to 3.0 mL of MVH solution with different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH radical scavenging activities of the MVH were determined as described by Li et al (2017) with slight modifications. Briefly, 1.0 mL of DPPH (0.1 mmol/L) diluted in ethanol was added to 3.0 mL of MVH solution with different concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Another relevant outcome of using HP as an environmentally-friendly extraction technology was reported for the extraction of astaxanthin (a natural carotenoid used as a colorant in animal feed, food and cosmetics) from shrimp shells, a by-product of shrimp processing. 133 The authors indicated that the maximum recovery of this carotenoid (71.1 μg g −1 ) was obtained by applying 200 MPa for 5 min with 20 mL ethanol per g shrimp shell. In addition, the authors also observed that the astaxanthin obtained from HP treatment displayed higher antioxidant activity than that isolated from the extraction at atmospheric pressure (43.6 μg g −1 ).…”
Section: Application Of Hp In Sustainable Extractionmentioning
confidence: 99%
“…Furthermore, residues of synthetic colorants produce toxic chemicals which have a harmful influence on fauna, flora, and human beings (Sinha et al, 2012a). Therefore, the increasing interest and demand for natural foods (Li et al, 2016), negative health and environmental issues of artificial dyes (Favati, King, Friedrich, & Eskins, 1988), and the high cost of artificial colorants (Li et al, 2016) have caused to an expanding global and economical market for natural colorants (Favati et al, 1988). These natural colorants can be used as additives or supplements in the healthy functional foods, livestock feed, cosmetic products, and pharmaceuticals (Boo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%